Retinal Vascular Autoregulation during Phase IV of the Valsalva Maneuver: An Optical Coherence Tomography Angiography Study in Healthy Chinese Adults - Zong, Yuan; Xu, Huan; Yu, Jian; Jiang, Chunhui; Kong, Xiangmei; He, Yi; Sun, Xinghuai (Frontiers in Physiology, 2017)
The impairment of retinal vascular autoregulation can be an early manifestation of many systemic and ocular diseases. Therefore, quantifying retinal vascular autoregulation in a noninvasive manner is very important. This study evaluated the effects of a Valsalva maneuver (VM)-induced blood pressure increases on retinal vascular autoregulation. Parafoveal and peripapillary retinal vessel density were measured with optical coherence tomography angiography before (baseline) and 5 seconds after each subject completed a VM (Phase IV [VM-IV]). Hemodynamic parameters and intraocular pressure (IOP) were examined. Blood pressure (systolic, diastolic, and mean arterial) and ocular perfusion pressure significantly increased during VM-IV, but IOP and heart rate (HR) did not change. The VM-induced blood pressure overshoot significantly decreased parafoveal (8.43%) and peripapillary (1.57%) perfused retinal vessel density (both P < 0.001). The response in the parafoveal region was greater than that in the peripapillary region (P < 0.001), and was age-dependent (r = 0.201, P < 0.05). Foveal avascular zone area detectable with OCTA significantly increased from baseline by 6.63% during VM-IV (P < 0.05). Autoregulatory responses to a VM did not show gender-related differences in either retinal region. The autoregulation of retinal vessels may vary in different regions of the fundus. Optical coherence tomography angiography could be a useful method for evaluating the autoregulation of the retinal vascular system.